CMR detects decreased myocardial deformation in asymptomatic patients at risk for heart failure - Hashemi, Djawid; Doeblin, Patrick; Blum, Moritz; Weiss, Karl Jakob; Schneider, Matthias; Korosoglou, Grigorios; Beyer, Rebecca Elisabeth; Pieske, Burkert; Edelmann, Frank; Kelle, Sebastian (Frontiers in Cardiovascular Medicine, 2023)
Aims: The main management strategy of heart failure with preserved ejection fraction (HFpEF) is prevention since HFpEF is associated with many cardiovascular (CV) risk factors, especially since HFpEF is linked to a high risk for both mortality and recurrent HF hospitalizations. Therefore, there is a need for new tools to identify patients with a high risk profile early. Regional strain assessment by CMR seems to be superior in describing deformation impairment in HF. The MyoHealth score is a promising tool to identify cardiac changes early. Methods and results: HF patients irrespective of LVEF and asymptomatic controls were recruited, and CMR based measures were obtained. For this analysis the asymptomatic control group (n=19) was divided into asymptomatic subjects without CV co-morbidities or evidence of cardiac abnormalities and (n=12) and asymptomatic subjects with CV co-morbidities or evidence of cardiac abnomalities (n=7). We performed CMR scans at rest and during a stress test using isometric handgrip exercise (HG). Assessing the MyoHealth score at rest revealed preserved regional strain in 85±9% of LV segments in controls, 73±11% in At Risk subjects and 73±8% in HFpEF patients. During stress the MyoHealth score was 84±7% in controls, 83±7 in At Risk subjects and 74±11 in HFpEF patients. Conclusion: In summary, we show for the first time that asymptomatic subjects with increased CV risk present with HFpEF like impaired myocardial deformation at rest, while they show results like controls under HG stress. The potential of preventive treatment in this group of patients merits further investigation in future.